THE EFFECT OF TASK-BASED LANGUAGE TEACHING AND ENGLISH GRAMMAR MASTERY TOWARD READING COMPREHENSION OF THE SECOND SEMESTER STUDENTS - Kumara, Gana; ., PADMADEWI; W, SUARNAJAYA, (Jurnal Pendidikan Bahasa Inggris, 2013)
Abstract This study focused on the effect of task based language teaching and grammar mastery toward studentsâ reading comprehension. It was an experimental study by making use of post test-only control group with 2 x 2 factorial design. The population of the study was 175 second semester students of the English Education Study Program of FKIP UNMAS Denpasar wherein 52 students were chosen as the sample through Intact Group Random Sampling. The research data were collected through a grammar mastery test and a reading comprehension test and were analyzed by using Two-Way ANOVA and Tukey test assissted by SPSS 16.0. The findings showed that, firstly, the students who were treated by TBLT achieved better reading comprehension than those who were treated by conventional method; secondly, there was an interactional effect between TBLT and grammar mastery upon the studentsâ reading comprehension; thirdly, the students with high grammar mastery gained higher reading comprehension score when they were treated by TBLT than by conventional method; and fourthly, there was significant difference in reading comprehension between the students who had low grammar mastery taught by using TBLT and those who were taught by conventional method. Â Â Keywords: task based language teaching, grammar mastery, reading comprehension.